Analysis of passenger transportation quality in Sevastopol - Lyudmila S. Plestzova; Marina N. Kripak; Larisa A. Kiyashko (International Journal of Advanced Studies, 2025)
Background. The priority tasks for improving the quality of services in the field of transport, the main problems associated with the organization of route transport and road traffic in the city of Sevastopol are considered. The quality of urban passenger transportation after optimization of the route network in Sevastopol is analyzed. The research considers specific features of Sevastopol, such as mountainous relief, narrow streets of historical buildings, uneven distribution of places of attraction and passenger flows, as well as unstable weather conditions. These factors significantly complicate the process of route network optimization and need to be taken into account in the development of any changes. In particular, we analyze the experience of implementing the system of “seamless” transfers, identifying both its positive sides (e.g., reducing duplication on certain sections) and negative consequences (increased travel time, reduced convenience for passengers).